Brief imagery rescripting vs. usual care and treatment advice in refugees with posttraumatic stress disorder: study protocol for a multi-center randomized-controlled trial. Issue 1 (1st January 2021) - Steil, Regina; Lechner-Meichsner, Franziska; Johow, Johannes; Krüger-Gottschalk, Antje; Mewes, Ricarda; Reese, Jens-Peter; Schumm, Hannah; Weise, Cornelia; Morina, Nexhmedin; Ehring, Thomas
ABSTRACT: Background : Many refugees have experienced multiple traumatic events in their country of origin and/or during flight. Trauma-related disorders such as posttraumatic stress disorder (PTSD) or complex PTSD (CPTSD) are prevalent in this population, which highlights the need for accessible and effective treatment. Imagery Rescripting (ImRs), an imagery-based treatment that does not use formal exposure and that has received growing interest as an innovative treatment for PTSD, appears to be a promising approach. Objective : This randomized-controlled trial aims to investigate the efficacy of ImRs for refugees compared to Usual Care and Treatment Advice (UC+TA) on (C)PTSD remission and reduction in other related symptoms. Method : Subjects are 90 refugees to Germany with a diagnosis of PTSD according to DSM-5. They will be randomly allocated to receive either UC+TA ( n = 45) or 10 sessions of ImRs ( n = 45). Assessments will be conducted at baseline, post-intervention, three-month follow-up, and 12-month follow-up. Primary outcome is the (C)PTSD remission rate. Secondary outcomes are severity of PTSD and CPTSD symptoms, psychiatric symptoms, dissociative symptoms, quality of sleep, and treatment satisfaction. Economic analyses will investigate health-related quality of life and costs. Additional measures will assess migration and stress-related factors, predictors of dropout, therapeutic alliance and session-by-session changes in trauma-related symptoms. Results and Conclusions : Emerging evidence suggests the suitability of ImRs in the treatment of refugees with PTSD. After positive evaluation, this short and culturally adaptable treatment can contribute to close the treatment gap for refugees in high-income countries such as Germany. Trial registration : German Clinical Trials Register under trial number DRKS00019876, registered prospectively on 28 April 2020. Highlights: Many refugees have experienced traumatic events. This trial investigates the efficacy of imagery rescripting, a short and culturally adaptable treatment that can contribute to close the treatment gap for refugees with posttraumatic stress disorder in high-income countries.